DEVELOPMENT OF USABILITY MODEL ON E-COMMERCE WEBSITE AND ITS IMPACT ON E-COMMERCE USERS USAGE CONTINUANCE - RUWAIDA NIM: 23416086, ARFI
Usability in the context of website is a site design and a specific functional feature that make e-commerce sites easier to use and users able to meet their goals through the e-commerce sites. Well-designed usability will result in continuous usage from users of e-commerce sites. Therefore, this study aims to determine the factors that can describe usability and recognize its effect on usage continuance. Based on previous studies, the hypothesized variables that describe usability are learnability, efficiency, memorability, accuracy, flexibility, emotion, and utility. Utility is a variable that represents the functional aspect of usability, so it is described in more detail in information search, display interface, and transaction variable. The usability factors will be used to explain the effect on usage continuance and usefulness as outcomes of use. Furthermore, there is a mediation effect on usability (second order) and usefulness to usage continuance. This study uses 505 data e-commerce users to test the hypothesis that has been designed. SEM (Structural Equation Modeling) is used to process the data that has been obtained. Goodness of fit of the measurement model and structural model of this research is quite good, so it can be concluded that memorability, accuracy, and utility are able to describe usability well. Usage continuance is only influenced by memorability, while usefulness is influenced by efficiency, accuracy, emotion, and utility. From the results of SEM, it is also known that the mediation effect of satisfaction on the relationship of usefulness to usage continuance proved to have an effect. In addition, multigroup SEM based on gender (female and male) and by age (under 23 and above 23 years) are performed to see the difference of research models through demographic aspects of e-commerce users. The result show that there are differences in sex groups and age groups. These results can be used by e-commerce providers to determine business strategies based on selected target markets.